Aspects and experiences of crisis in rural Greece. Narratives of rural resilience. (May 2017) - Anthopoulou, Theodosia; Kaberis, Nikolaos; Petrou, Michael
Abstract: The purpose of this paper is to explore aspects, dynamics and experiences of the crisis in the Greek countryside. The 'rural' is emerging in public discourse as a resilient milieu of solidarity, of social innovation, and of opportunities for employment, especially in farming and in rural entrepreneurship. It seems that the crisis has contributed to triggering social constructions of 'idyllic rurality' which generated counterurbanisation tendencies and expectations for urbanites to return back to the land. However, those who had remained in rural areas and in farming were already been confronted with the prolonged crisis of the agricultural sector (CAP reforms and market liberalization), now coupled with the severe impact of the recent economic and financial crisis in Greece. Drawing on narratives of farmers and incomers in two rural areas, the paper investigates experiences and strategies to deal with the crisis, in the framework of work and family and in the context of discourses on rural resilience. Personal accounts reveal that remaining or returning to rural areas often conceal cases of underemployment and social deprivation and that, both farmers and incomers are not explicitly supported by policy makers. Highlights: Narratives of rural resilience by farmers and incomers within recent economic crisis. Analysis of crisis-counterurbanisation as experience of installation in the rural milieu. Economic crisis is experienced by farmers as "crisis within a crisis (agricultural)". Rural resilience may mask underemployement and social deprivation. Rural resilience should be accompanied by public policies to support farmers and incomers.